Diagnostic potential of salivary IL-1β, IL-8, SAT, S100P, and OAZ1 in oral squamous cell carcinoma, oral submucous fibrosis, and oral lichen planus based on findings from a Sri Lankan cohort - Kalpani Senevirathna; Thilini Anupama Nanayakkarawasam Mahakapuge; Nadeeka U. Jayawardana; Jayanthe Rajapakse; Chandrika Udumalagala Gamage; Bimalka Seneviratne; Unil Perera; Kehinde Kazeem Kanmodi; Ruwan Duminda Jayasinghe (Scientific Reports)
Abstract The research examined the salivary concentrations of various biomarkers, such as OAZ1, SAT, S100P, IL-1β, and IL-8 aiming to detect early-stage oral squamous cell carcinoma (OSCC). These biomarkers show potential as indicators for detecting both pre-cancerous and cancerous states within the oral cavity. Analyzing these specific molecules in saliva could help clinicians enhance diagnostic accuracy and refine early detection methods for OSCC. The research encompassed a cohort of nine OSCC patients, ten with oral submucous fibrosis (OSF), eleven individuals with oral lichen planus (OLP), and ten healthy controls. The study focused on assessing the expression levels of key biomarkers—IL-1β, IL-8, SAT, S100P, and OAZ1 mRNA—in extracellular RNA extracted from saliva samples. This evaluation was conducted using real-time quantitative reverse transcription polymerase chain reaction (RT-qPCR) with sequence-specific primers. Additionally, receiver operating characteristic curve (ROC) curve analysis was employed to gauge the efficacy of these biomarkers in detecting OSCC. Based on the results we observe, when these five biomarkers are used together, they give a 90% predictive probability for patients with OLP, an 80% predictive probability for OSF, and an impressive 100% predictive probability for patients with OSCC (AUC = 1.000, p = 0.000). This study demonstrates the efficacy of salivary transcriptome diagnostics in detecting OSCC. This novel clinical technique has the potential to be a powerful, efficient, and reliable tool for early detection of cancer. Salivary transcriptomes can be further analyzed to evaluate their effectiveness in other important illness contexts and for regular health monitoring.